The Use of a Geographical Information System (GIS) as a Spatial Decision Support System: Processing Planning Applications in Hilly Areas - Abdul Wahab, Abbas (2001)
Decision-making pertaining to development control has been increasingly complex as urbanization extends into environmentally sensitive hilly areas. Coupled to that, the traditional data analysis method of sieving maps is very cumbersome and inefficient for processing planning applications. Here a Geographical Information System [GIS] is seen as the ideal tool of the information age to improve the current inadequacies of the present planning system. Henceforth, the study aimed to adapt GIS as a decision support tool for processing planning applications specifically, in hilly areas. The study methodology basically involved the identification of a problem statement, formulation of goal and objectives, literature review on the application of GIS in local planning, the development of a planning data model and the design of a planning expert system. The planning data model consolidated relevant data for processing potential development in hilly areas. Hence, it was structured into common groups namely town planning, administration, utilities, environment and transportation. The principle object behind data analysis was to query site suitability and to determine whether the detailed proposals conformed to planning requirements. To aid decision-making, the decision support system employed a planning expert system. The knowledge base rules of the planning expert system incorporated planning guidelines development in hilly areas. An inference engine consisted of various scripts based on Boolean argument was designed to enable comparative assessment between detail proposals and planning parameters and provided technical advice to support or reject an application. A customised pull-down menu was designed to simplify data query and data retrieval. The study found that although GIS was effective at data analysis, for the moment, it would be of limited success in processing planning applications because there are many types of planning issues to consider. This would require further development of GIS analytical techniques before it could comprehensively process planning applications. The expert system while effective, depended on a standard format to process layout plans. Overlaying regularly used for data analysis but proved more effective when combined with other techniques e.g. buffering or spatial analysis. Although planning criteria were available, they had to be reviewed to weed out ambiguous terminologies. Attributes tables were vital to ensure the expert system worked because the inference engine is critical where data are kept. Since GIS was in various stages of implementation, it was concluded GIS could serve as a decision support system for processing planning applications in hilly areas. Further research was still required to develop new planning expert systems in various sectoral studies e.g. transportation planning. This included the development of digital supporting database, expansion in the scope and depth of data analysis, development of planning design models, fine-tuning planning criteria and the establishment a uniform digital format for the preparation of layout plans.